Influence of iron oxides on the properties of unfluoridated enamel frit glass and coatings - Ryzhova, Olga; Khokhlov, Maxim; Goleus, Victor; Nosenko, Alexander (Publishing House of Lviv Polytechnic National University, 2015)
The influence of iron oxides on the properties of unfluoridated enamel glass frit and coatings in the system of Na2O – B2O3– SiO2 has been studied. It has been determined that the introduction of Fe2O3 additive in the amount of 0.4 mol % instead of SiO2 into an unfluoridated glass enamels improves the optical-color characteristics of the coatings, pigmented with selenium cadmium red. Досліджено вплив оксидів заліза на властивості безфлуористих емалевих склофрит та покриттів в системі Na2O– B2O3– SiO2. Встановлено, що введення додатку Fe2O3 у кількості 0,4 мол.% замість SiO2 в безфлуористій склоемалі покращує оптико-колірні характеристики покриттів, забарвлених червоним селенокадмієвим пігментом.
Вплив оксидів заліза на властивості безфлуористих емалевих склофрит та покриттів
Keywords: unfluoridated glass frit; brightly pigmented coating; iron oxide; microstructure; безфлуористі склофрити; яскраво забарвлені покриття; оксид заліза; мікроструктура